Sistem Rekomendasi Pekerjaan di bidang IT Menggunakan Algoritma Content-Based Filtering - Crismastiana Koloman; Raihan Maulana; Raisya Dwi Zahra Putri; Wahyu Abadi Harahap (Pusat Riset dan Inovasi Nasional, 2023)
Rapid growth in the Information Technology (IT) industry has created an abundance of career opportunities, but job seekers often face difficulty in finding jobs that match their background and skills. To overcome this challenge, this research presents a “Job Recommendation System” that focuses on the IT industry. The method used in this research is